FACTORS THAT INFLUENCE THE INTENTION TO PURCHASE LOCAL FASHION PRODUCTS AMONG BRAND X CONSUMERS IN JAKARTA - Rismadhani, Nanda Talia; Febrilia, Ika; Monoarfa, Terrylina Arvinta (Univesitas Muhammadiyah Tangerang, 2023)
This research aims to determine the influence of social media and celebrity supporters on purchasing intentions for local fashion products, a case study of Brand X consumers in Jakarta. This research is quantitative with correlational research methods. The population involved was all consumers of Brand The criteria used in this research were Brand The data analysis technique used in this research is multiple linear regression using SPSS version 25.0. The research results obtained show that there is a significant positive influence between social media and the intention to purchase local fashion products. Then, between celebrity supporters and intention to buy local fashion products there was a significant positive influence. Then, social media and celebrity supporters have a significant positive influence on the intention to purchase local fashion products.